Biophysically motivated efficient estimation of the spatially isotropic R2* component from a single gradient‐recalled echo measurement. Issue 5 (10th July 2019) - Papazoglou, Sebastian; Streubel, Tobias; Ashtarayeh, Mohammad; Pine, Kerrin J.; Edwards, Luke J.; Brammerloh, Malte; Kirilina, Evgeniya; Morawski, Markus; Jäger, Carsten; Geyer, Stefan; Callaghan, Martina F.; Weiskopf, Nikolaus; et al.
Abstract : Purpose: To propose and validate an efficient method, based on a biophysically motivated signal model, for removing the orientation‐dependent part of R 2 * using a single gradient‐recalled echo (GRE) measurement. Methods: The proposed method utilized a temporal second‐order approximation of the hollow‐cylinder‐fiber model, in which the parameter describing the linear signal decay corresponded to the orientation‐independent part of R 2 * . The estimated parameters were compared to the classical, mono‐exponential decay model for R 2 * in a sample of an ex vivo human optic chiasm (OC). The OC was measured at 16 distinct orientations relative to the external magnetic field using GRE at 7T. To show that the proposed signal model can remove the orientation dependence of R 2 *, it was compared to the established phenomenological method for separating R 2 * into orientation‐dependent and ‐independent parts. Results: Using the phenomenological method on the classical signal model, the well‐known separation of R 2 * into orientation‐dependent and ‐independent parts was verified. For the proposed model, no significant orientation dependence in the linear signal decay parameter was observed. Conclusions: Since the proposed second‐order model features orientation‐dependent and ‐independent components at distinct temporal orders, it can be used to remove the orientation dependence of R 2 * using only a single GRE measurement.